Smoke as Spiritual Communication: An Ethnographic Study of Ritual Practices in Indonesian Religious and Indigenous Belief Systems - Betty Tresnawaty; Nur’aini Azizah; Wardatul Hayat Adnan (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2026)
Religious and indigenous belief systems across Indonesia are transmitted intergenerationally and are deeply embedded in ritual practices rich in symbolic meaning. One recurring element in many of these rituals is the use of smoke, produced from burning plants, resins, incense, and other organic materials. Despite its widespread presence, the symbolic meanings and communicative functions of smoke within ritual contexts remain underexplored in scholarly discussions on religion and culture. This study focuses on ritual practitioners from several Indonesian ethnic communities, particularly the Sundanese, Javanese, and Batak groups, whose ritual traditions continue to preserve the spiritual use of smoke in both religious and indigenous belief practices. The study aims to examine how these communities interpret and utilize smoke in their spiritual rituals.communities. Employing an ethnographic approach, primary data were collected through in-depth interviews with 23 ritual practitioners from diverse religious and belief backgrounds among Sundanese, Javanese, and Batak communities. The data were analyzed thematically to identify patterns of meaning and ritual function. The findings reveal that smoke is understood not merely as a ritual accessory, but as a medium of spiritual communication—facilitating interaction with spiritual entities, mediating transcendental connections, and fostering personal spiritual well-being. These results contribute to broader discussions in religious, social, and cultural studies by highlighting smoke as a symbolic communicative device embedded in lived religious experience. The study also opens comparative possibilities for understanding similar ritual expressions in other cultural contexts.